The Clinical Microsystems Clerkship at University of California, San Francisco: Integrating Clinical Skills and Health Systems Improvement for Early Medical Students. (3rd October 2022) - Chang, Anna; Pierluissi, Edgar; Cornes, Susannah; Ishizaki, Allison; Teherani, Arianne; Davis, John A.; Hauer, Karen E.; Lucey, Catherine R.
Abstract : Problem: Medical educators recognize that partnering actively with health system leaders closes significant health care experience, quality, and outcomes gaps. Medical schools have explored innovations training physicians to care for both individual patients and populations while improving systems of care. Yet, early medical student education fails to include systems improvement as foundational skills. When health systems science is taught, it is often separated from core clinical skills. Approach: The Clinical Microsystems Clerkship at the University of California, San Francisco School of Medicine, launched in 2016, integrates clinical skills training with health systems improvement from the start of medical school. Guided by communities of practice and workplace learning principles, it embeds first-year and second-year students in longitudinal clinical microsystems with physician coaches and interprofessional clinicians one day per week. Students learn medical history, physical examination, patient communication, interprofessional teamwork, and health systems improvement. Assessments include standardized patient examinations and improvement project reports. Program outcome measures include student satisfaction and attitudes, clinical skills performance, and evidence of systems improvement learning, including dissemination and scholarship. Outcomes: Students reported high satisfaction (first-year, 4.10; second-year, 4.29, on a scale of 1–5) and value (4.14) in their development as physicians. Clinical skills assessment accuracy was high (70%–96%). Guided by interprofessional clinicians across 15 departments, students completed 258 improvement projects in 3 health systems (academic, safety net, Veterans Affairs). Sample projects reduced disparities in hypertension, improved opiate safety, and decreased readmissions. Graduating students reported both clinical skills and health systems knowledge as important to physician success, patient experience, and clinical outcomes (4.73). Most graduates discussed their projects in residency applications (85%) and disseminated related papers and presentations (54%). Next Steps: Integrating systems improvement, interprofessional teamwork, and clinical skills training can redefine early medical student education. Health system perspectives, long-term outcomes, and sustainability merit further exploration.